Improving the qualifications of doctors on the base of intelligent decision support systems - О. Стенін; В. Пасько; О. Лісовиченко; В. Солдатов (Adaptivni Sistemi Avtomatičnogo Upravlinnâ)
The development of medical intelligent decision-making support systems (IDSS) provides an opportunity not only for advisory assistance at various stages of the medical and diagnostic process, but also the opportunity to improve the qualifications of doctors when using IDSS. The use of IDSS contributes to the acquisition of additional knowledge by the doctor in the case of an incomplete manifestation of the clinical picture and in complex cases, in particular, in rare diseases. This article proposes the structure and composition of the IDSS of medicinal decisions, for which it is proposed to use a combined approach based on the frame structure of the knowledge model using production rules. The production rules issue an explanation understandable to the doctor, which includes a list of signs, taking into account which the diagnostic hypothesis is formed. As an example, several production rules are given regarding the identification of possible diseases of patients based on the level of general blood analysis indicators. The essence of the mechanism of fuzzy logical derivation is to determine the dependence of the output logistic variable (consequent) on the corresponding input logistic variable (antecedent) taking into account the reliability factor and the knowledge importance factor.